Health and zoonotic Infections of snow leopards Panthera unica in the South Gobi desert of Mongolia. Issue 1 (1st January 2019) - Esson, Carol; Skerratt, Lee F.; Berger, Lee; Malmsten, Jonas; Strand, Tanja; Lundkvist, Åke; Järhult, Josef D.; Michaux, Johan; Mijiddorj, Tserennadmid Nadia; Bayrakçısmith, Rana; Mishra, Charudutt; Johansson, Örjan
ABSTRACT: Background : Snow leopards, Panthera uncia, are a threatened apex predator, scattered across the mountains of Central and South Asia. Disease threats to wild snow leopards have not been investigated.Methods and Results : Between 2008 and 2015, twenty snow leopards in the South Gobi desert of Mongolia were captured and immobilised for health screening and radio-collaring. Blood samples and external parasites were collected for pathogen analyses using enzyme-linked immunosorbent assay (ELISA), microscopic agglutination test (MAT), and next-generation sequencing (NGS) techniques. The animals showed no clinical signs of disease, however, serum antibodies to significant zoonotic pathogens were detected. These pathogens included, Coxiella burnetii, (25% prevalence), Leptospira spp., (20%), and Toxoplasma gondii (20%). Ticks collected from snow leopards contained potentially zoonotic bacteria from the genera Bacillus, Bacteroides, Campylobacter, Coxiella, Rickettsia, Staphylococcus and Streptococcus .Conclusions : The zoonotic pathogens identified in this study, in the short-term did not appear to cause illness in the snow leopards, but have caused illness in other wild felids. Therefore, surveillance for pathogens should be implemented to monitor for potential longer- term disease impacts on this snow leopard population.